Imperfectionist: A Friendship-grounded Approach to Academic Library Instruction - Edwards, Ashley; Lane, Julia (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2023)
This article focuses on a form of embedded instruction, wherein library employees work weekly within a student space, in this case the Indigenous Student Centre at Simon Fraser University in what is colonially known as British Columbia, Canada. As we continued to learn together and deepen our appreciation of Sḵwx̱wú7mesh scholarship and theory -- scholarship and theory Indigenous to the lands we occupy -- we recognized deep resonance with our understandings and approaches. In particular, Denise Findlay’s (Sḵwx̱wú7mesh) sharing about eslhélha7kwhiwsm and imperfect friendship have shaped our understandings of both our friendship and our role as teachers. Writing in an epistolary form, we dialogue about the time we spend together in the Indigenous Student Centre and how that time has allowed us to develop and appreciate a friendship-grounded approach to teaching and learning. This article invites readers into a dialogue between the authors, whose relationship initially developed through work collaborations and grew into a real-life friendship. By sharing stories, questions, and connections with what we are reading and learning, the authors encourage one another, and simultaneously the reader, to consider the possibilities of imperfection, humility, friendship, and radical care in academic library instruction beyond the classroom.